Modulation of the Sympatho-Vagal Balance during Sleep: Frequency Domain Study of Heart Rate Variability and Respiration - Cabiddu, Ramona; Cerutti, Sergio; Werner, Sandra; Viardot, Geoffrey; Bianchi, Anna M. (Frontiers in Physiology, 2012)
Sleep is a complex state characterized by important changes in the autonomic modulation of the cardiovascular activity. Heart rate variability (HRV) greatly changes during different sleep stages, showing a predominant parasympathetic drive to the heart during non-rapid eye movement sleep (NREM) and an increased sympathetic activity during rapid eye movement sleep (REM). Respiration undergoes important modifications as well, becoming deeper and more regular with deep sleep and shallower and more frequent during REM. The aim of the present study is to assess both autonomic cardiac regulation and cardiopulmonary coupling variations during different sleep stages in healthy subjects, using spectral and cross-spectral analysis of the HRV and respiration signals. Polysomnographic sleep recordings were performed in 11 healthy women and the HRV signal and the respiration signal were obtained. The spectral and cross-spectral parameters of the HRV signal and of the respiration signal were computed at low frequency (LF) and at breathing frequency (high frequency, HF) during different sleep stages. Results attested a sympatho-vagal balance shift towards parasympathetic modulation during NREM sleep and towards sympathetic modulation during REM sleep. Spectral analysis of the HRV signal and of the respiration signal indicated a higher respiration regularity during deep sleep, and a higher parasympathetic drive is also confirmed by an increase in the coherence between the HRV and the respiration signal in the HF band during NREM sleep. Our findings about sleep stage-dependent variations in the HRV signal and in the respiratory activity are in line with previous evidences and confirm spectral analysis of the HRV and the respiration signal to be a suitable tool for investigating cardiac autonomic modulation and respiration activity during sleep.